Utilization of modern contraception and determinants among HIV positive women in Ethiopia: a systematic review and meta-analysis - Moges Muluneh Boke; Alehegn Bishaw Geremew; Asmamaw Atnafu; Mesfin Wudu Kassaw; Tsegaye Gebremedhin Haile (BMC Women's Health)
Abstract Background The burden of pediatric HIV/AIDS, mother-to-child transmission rate, and unintended pregnancy among HIV-positive women remain high in sub-Saharan Africa, including Ethiopia. Provision of contraceptives is an undeniable strategy to overcome the risks. However, pooled data to provide informed decisions on modern contraceptive use among HIV-positive women attending ART clinics in Ethiopia are meager. Hence, this review aimed to estimate the magnitude of modern contraception, and revisable long act contraceptives methods (RLCM) use and associated factors among HIV positive ART clinic attending women. Methods A systematic review and meta-analysis was conducted using PubMed, Google, Cochrane library, Web of Science, Google Scholar, and Scopus database. A funnel plot and Egger’s regression test were used to assess publication bias. Heterogeneity of studies was assessed using I-square statistics and the Joanna Briggs Institute (JBI) quality assessment tool was applied to ensure the quality of the included articles. We employed a random-effect model to pool the national utilization of modern contraceptives and the effect size of associated factors. We conducted sub-group analysis by regions to control heterogeneity and to detect variation. Results A total of 21 studies were included in the meta-analysis. The magnitude of pooled utilization of modern contraceptive and RLCM was 60% [95% CI: 52–68] and 11%, [95% CI: 8–14], respectively. In the random effect model, young women [OR = 2.36, 95% CI: 1.78–3.13], attending secondary school and above [AOR = 1.34, 95% CI: 1.06–1.69], having two or more live children [AOR = 1.84, 95% CI: 1.46–2.34], discussion with a husband [AOR = 2.92, 95% CI: 2.39–3.57], CD4 > 250cells/mm3 [AOR = 1.59, 95% CI: 1.08–2.33], and using HAART [AOR = 1.71, 95% CI: 1.35–2.15] increased odds of modern contraceptive methods utilization. Conclusion Overall the utilization of RLCM among modern contraceptive users HIV positive women is low. Therefore, to improve the uptake of RLCM among modern contraceptive users HIV positive women, policymakers and program designers need to take into account age and educational levels of women and programs which enhance reproductive health consultation habit between couples. Moreover, integration of family planning services to ART clinics needs to be strengthened.